PENGARUH EQUITY SENSITIVITY, ETHICAL SENSITIVITY, DAN LOCUS OF CONTROL TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI: (Studi Kasus pada Mahasiswa Akuntansi Universitas Hindu Indonesia) - Devia Julyanti, Ni Kadek; Sudiana, I Wayan (Hita Akuntansi dan Keuangan, 2022)
Ethical behavior is behavior that is in accordance with social norms related to right and good actions, ethical behavior can determine individual qualities. This study aims to determine the effect of equity sensitivity, ethical sensitivity, and locus of control on the ethical behavior of students in the Accounting Study Program at the Hindu University of Indonesia. This research is a type of quantitative research. The population of this study were active students of the Accounting Study Program at the Hindu University of Indonesia with a sample of 265 students. The sampling technique used is probability sampling technique using the slovin method of calculation. The data source is primary data which is processed using SPSS 25 Version for Windows which is obtained through questionnaires. The data analysis technique used is multiple linear regression analysis, coefficient of determination, t statistical test, and F statistical test. The outcomes of this study concluded that equity sensitivity and ethical sensitivity have a positive and significant effect on students's ethical behavior, while locus of control has a positive and insignificant effect on students's ethical behavior.